Bioenergy recovery from olive mill effluent in a hybrid reactor - Gonçalves, Marta R. (2012)
An anaerobic hybrid reactor was tested in the treatment of raw olive mill effluent (OME)without water dilution, chemical correction and any pretreatment. A feeding strategy was applied by increasing progressively the OME volume fraction from 8% to 83% in the feed mixture combined with an OME complementary substrate (piggery effluent). A biogas production of 3.16 m3 m-3 d-1 was achieved at an organic loading rate of COD at 7.1 kg m-3 d-1, when the highest fraction of OME was added to the influent (volume fraction of 83%; COD concentration fraction of about 94%). At these conditions, the degradation of olive mill effluent occurred without any inhibition. The reactor was capable to digest an acid influent (pH = 4.7), revealing a high buffering capacity. The increase of influent phenols concentration from 0.87 kg m-3 to 2.31 kg m-3 did not influence the reactor removal capacity (phenolic fraction removal from 51% to 61%). Biomass acclimation to OME was accomplished by using a feeding strategy based on effluents complementarity. Furthermore, it was demonstrated that the hybrid digester was able to recover after an accidental overload, and the packing material on the top of the unit prevented excessive loss of biomass. Comparatively to the classic configuration digesters, the hybrid digester is an effective alternative to maximize bioenergy recovery from OME.